2017
DOI: 10.1186/s40066-017-0103-y
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ knowledge and perception of postharvest physiological deterioration in cassava storage roots in Ghana

Abstract: Background: In spite of the essential role of cassava in ensuring household food security and employment for most rural farm households, postharvest physiological deterioration (PPD) of the roots which is serious abiotic stress in cassava renders the roots unmarketable, thereby reducing the economic value of the crop. This paper investigates farmers' knowledge and perception of PPD in the storage roots of cassava among smallholders in Ghana. Methods:A participatory rural appraisal and a formal survey involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 6 publications
1
5
0
Order By: Relevance
“…PPD is the primary cause for post-harvest deterioration in cassava. The results are in consonance with research results by [23] who reported PPD as one of the major post-harvest constraints for cassava in Ghana. This is the case because currently, there is no effective control measure for PPD for flesh cassava roots apart from preventive approaches aimed at delaying on-set and development of PPD [16].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…PPD is the primary cause for post-harvest deterioration in cassava. The results are in consonance with research results by [23] who reported PPD as one of the major post-harvest constraints for cassava in Ghana. This is the case because currently, there is no effective control measure for PPD for flesh cassava roots apart from preventive approaches aimed at delaying on-set and development of PPD [16].…”
Section: Discussionsupporting
confidence: 91%
“…They further pointed out that high temperatures and sunny conditions favoured the development of PPD. Knowledge of these factors that cause and influence development of PPD is crucial among farmers as it guides the farmers on local preventative methods that work by modifying the environmental conditions to extend shelf-life of fresh cassava roots [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pest and disease attack is also a very serious cause of cassava post-harvest losses faced that can reduce the nutritional quality of cassava. According to Prempeh et al (2017), pest and diseases (pathogens) were among the main causes of post physiological deterioration in cassava as perceived by the farmers…”
Section: Causes Of Post-harvest Losses In Cassavamentioning
confidence: 99%
“…Cassava roots rot within 2-3 days after being unearthed as the produce is of very high moisture content [11]. A recent survey of farmers in Ghana detailed cassava takes an average of 3 days for the roots to decay after harvest [16]. The rapid deterioration consequentially affects marketing and eating quality.…”
Section: Introductionmentioning
confidence: 99%